Whole-Genome Comparative Analysis of Salmonella enterica Serovar Newport Strains Reveals Lineage-Specific Divergence. (1st April 2017) - Zheng, Jie; Luo, Yan; Reed, Elizabeth; Bell, Rebecca; Brown, Eric W.; Hoffmann, Maria
Abstract : Salmonella enterica subsp. enterica serovar Newport has been associated with various foodborne outbreaks in humans and animals. Phylogenetically, serovar Newport is one of several Salmonella serovars that are polyphyletic. To understand more about the polyphyletic nature of this serovar, six food, environment, and human isolates from different Newport lineages were selected for genome comparison analyses. Whole genome comparisons demonstrated that heterogeneity mostly occurred in the prophage regions. Lineage-specific characteristics were also present in the Salmonella pathogenicity islands and fimbrial operons.